New tetranuclear manganese clusters with [MnII3MnIII] and [MnII2MnIII2] metallic cores exhibiting low and high spin ground state. Issue 17 (24th March 2016) - Sobocińska, M.; Antkowiak, M.; Wojciechowski, M.; Kamieniarz, G.; Utko, J.; Lis, T.
Abstract : Two tetranuclear mixed-valent clusters with the metallic [MnII3Mn III ] and [MnII2MnIII2] cores were synthesized as molecular nanomagnets with the low and high spin in the ground state. Abstract : Two tetranuclear mixed-valent clusters, [MnII3Mn III Cl(Ph3 CCOO)4 (CH3 OCH2 CH2 O)4 (CH3 CN)]·0.4C6 H5 CH3 ·0.6CH3 CN (1 ) with an unprecedented [MnII3Mn III ] core and [MnII2MnIII2Cl4 (CH3 OCH2 CH2 O)6 ] (2 ), were synthesized and characterized by single-crystal X-ray diffraction and magnetic measurements. Their properties were analyzed in the framework of phenomenological modelling and DFT calculations, showing acceptable agreement between theory and experiment. Both building blocks [MnII3Mn III ] and [MnII2MnIII2] provide good examples of bipartite systems with the lowest S T = 1/2 and highest S T = 9 magnetic ground states available for them. The topology of the magnetic interactions in the [MnII3Mn III ] core provides a suitable template for the molecular qubit implementation and the stability of the spin-1/2 ground state strongly depends on the antiferromagnetic Mn II –Mn II coupling.